2006
DOI: 10.1029/2005jd006541
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of torrential rain events to the sea surface temperature based on high‐resolution numerical forecasts

Abstract: [1] Torrential rains often occur in the western Mediterranean region during the fall season when the Mediterranean Sea is still warm. The Mediterranean Sea acts in moistening and warming the low level of the atmosphere. Then, the southerly to easterly flow that prevails before and during torrential rainfall events, transports the conditionally unstable air toward the coasts where the convection can develop often triggered by a flow interaction with orography. This study examines the sensitivity to the sea surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
111
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 32 publications
14
111
0
2
Order By: Relevance
“…It results in an increase of the available energy and moisture for the atmospheric convection and consequently for precipitation. Lebeaupin et al (2006) highlighted that an SST increase induces systematically a CAPE (convective available potential energy) increase. Giordani and Caniaux (2001) have shown that the differential surface heating/moistening and thus the spatial variability of surface fluxes can be a significant source of ageostrophy, vertical velocity and vorticity for the atmosphere that plays a fundamental role in the cyclone development.…”
Section: A Sanna Et Al: Effect Of a High-resolution Marine Model Onmentioning
confidence: 99%
“…It results in an increase of the available energy and moisture for the atmospheric convection and consequently for precipitation. Lebeaupin et al (2006) highlighted that an SST increase induces systematically a CAPE (convective available potential energy) increase. Giordani and Caniaux (2001) have shown that the differential surface heating/moistening and thus the spatial variability of surface fluxes can be a significant source of ageostrophy, vertical velocity and vorticity for the atmosphere that plays a fundamental role in the cyclone development.…”
Section: A Sanna Et Al: Effect Of a High-resolution Marine Model Onmentioning
confidence: 99%
“…To study the coupled processes, the system is run either in the full interactive coupled mode or in the more traditional way in which only the ocean model is driven by the imposed atmospheric forcing. It is applied to the same three Mediterranean heavy precipitation events as those simulated by Lebeaupin et al (2006) and Lebeaupin Brossier et al (2008) (Figure 1(b)), which enables comparison with those studies. Additional sensitivity experiments allow us to see the impact of the different components of the intense atmospheric forcing (precipitation, low-level winds and air-sea fluxes) on the Ocean Mixed Layer (OML).…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean Sea contributes to fuelling these heavy precipitating systems in heat and moisture (Millan et al, 1995;Romero et al, 1997;Pastor et al, 2001;Homar et al 2003;Lebeaupin et al, 2006;Lebeaupin Brossier et al, 2008) and could also play a part in amplifying floods when the swell and waves perturb the river runoff. Based on convective scale numerical simulations of three torrential rainfall events over southeastern France, Lebeaupin et al (2006) and Lebeaupin Brossier et al (2008) have shown that the atmospheric convection intensity and consequently the surface rainfall totals are notably sensitive to the energy available in the atmospheric low levels supplied by the sea through the surface heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations